2018
DOI: 10.1080/23746149.2018.1428915
|View full text |Cite
|
Sign up to set email alerts
|

The electron density delocalization of hydrogen bond systems

Abstract: Recent experimental and theoretical researches have gradually proved that hydrogen bond (H-bond) interactions are not simple traditionally considered electrostatic interaction. Instead, they involve electron density delocalization. In this work, we outline the studies of electronic structures of the H-bond systems in water systems and biological organic molecules systems. Theoretical researches based on the first-principles method have found important evidences for electron density delocalization in H-bond reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 135 publications
0
41
0
Order By: Relevance
“…1c shows the crystal structure of ᴅ-hydantoinase [90] . They proposed that the intrinsic fluorescence did not originate from any aromatic residues, and that formation of hydrogen bonds between C=O and N-H groups of these species caused the inter-or intramolecular electron delocalization [91] . Rinaldi et al observed the green emission from poly(ValGlyGlyLeuGly) amyloid-like fibrils in 2007(Fig.…”
Section: Natural Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…1c shows the crystal structure of ᴅ-hydantoinase [90] . They proposed that the intrinsic fluorescence did not originate from any aromatic residues, and that formation of hydrogen bonds between C=O and N-H groups of these species caused the inter-or intramolecular electron delocalization [91] . Rinaldi et al observed the green emission from poly(ValGlyGlyLeuGly) amyloid-like fibrils in 2007(Fig.…”
Section: Natural Polymersmentioning
confidence: 99%
“…Additionally, xylitol exhibits RTP. Recently, Wang's group have summarized the electron density delocalization of hydrogenbonded systems [91] . It is generally agreed that the hydrogen bonds involve not only an electrostatic interaction, but they also induce electron density delocalization [155][156][157] .…”
Section: Clusteroluminogens Without Aromatic Ringsmentioning
confidence: 99%
“…1) Classical continuum thermodynamics [43][44][45][46][47] embraced the dielectrics, diffusivity, surface stress, viscosity, latent heat, entropy, nucleation, and liquid/vapor phase transition in terms of free energy, though this approach has faced difficulties in dealing with solvation dynamics and the properties of water and ice.…”
Section: Wonders Of H2o Molecular Undercoordination and Hydrationmentioning
confidence: 99%
“…shows that the -(15− 20) C ice and the 25 C water share the same skin supersolidity -identically shortened and stiffened H-O bond.DFT calculations by Wang and collaborators[47,83] examined the site-resolved electronic binding energy and H−O stretching vibration frequency for medium sized (H2O)n clusters (n = 17-25). They classify the H−O bonds into five groups: the dangling H−O bonds, the H−O bonds associated with the dangling H2O molecules, those with undercoordinated H2O molecules without dangling H−O bonds, those forming the tetrahedral-coordination of the central H2O and the others in its neighbor four molecules.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30] From the classical perspective, its essence is electrostatic interaction or dipole-dipole forces; [31,32] however, several recent experimental and theoretical studies have presented different views. [33][34][35][36][37][38] The dominating "electrostatic factors" must be strongly antagonistic to H-bond formation, which was demonstrated by studying a class of H-bond complexes between closed-shell ions of similar charge. [34] In addition, the donor-acceptor orbital interactions between electron lone pairs with anti-bond X-H show a number of magnitude contributions to the H-bond strength, which are special properties of the H-bonds.…”
Section: Introductionmentioning
confidence: 99%